FK506-binding proteins 12 and 12.6 (FKBPs) as regulators of cardiac Ryanodine Receptors: Insights from new functional and structural knowledge. Issue 5 (3rd September 2017) - Gonano, Luis A.; Jones, Peter P.
ABSTRACT: Ryanodine Receptors (RyRs) are intracellular Ca 2+ channels that mediate Ca 2+ flux from the sarco(endo)plasmic reticulum in many cell types. The interaction of RyRs with FK506-binding proteins (FKBPs) has been proposed as an important regulatory mechanism, where the loss of this interaction leads to channel dysfunction. In the heart, phosphorylation of RyR has been suggested to disrupt the RyR-FKBP interaction promoting altered Ca 2+ signaling, heart failure and arrhythmias. However, the functional result of FKBP interaction with RyR and how this interaction is regulated remains highly controversial. Recently, high resolution structures of RyR have provided novel aspects to the ongoing debate. This review will discuss the most recent functional data in light of these new structures.